REVISITING THE REASONABLENESS OF MAHR IN INDONESIA, INDIA, PAKISTAN AND BANGLADESH: A Multilayered Comparative Analysis - Musyaffa Amin Ash Shabah; JM Muslimin; Abdurrahman Dahlan; Soleh Samy (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2026)
Social status, cultural pressures, and economic stratification often drive the high value of marriage dowries. This study analyzes the social and cultural influences on dowry practices in Indonesia, India, Bangladesh, and Pakistan. It formulates a reconstruction of the determination of dowry grounded in the principles of fairness and justice. This study is normative-empirical, using a qualitative approach with a multilayered comparative approach, both in social, cultural, and legal aspects of dowry determination, which is then analyzed using the IRAC (Issue, Rule, Argument, and Conclusion) method. The results of the study show that although dowry in Islamic law functions as a theological right of the wife and financial protection, in practice, dowry is often influenced by socio-economic and cultural factors, making it a symbol of social status, a burdensome cultural pressure, and even a source of dowry-based violence. This study also identifies significant challenges in law enforcement regarding dowry, despite regulations governing it. Therefore, it is necessary to reconstruct the determination of dowry by prioritizing the principles of fairness, distributive justice, and integration between legal regulations and human values to prevent harmful dowry practices. This will create a legal system that is responsive to social dynamics, protects women's rights, and ensures justice for both parties in marriage, free from irrational social and cultural pressures.